Digital Public Relations of Partai Keadilan Sejahtera in Attracting Young Voters - Teguh, Monika; Kayana, Dheandra Mutiara; Haryono, Cosmas Gatot; Handi, Esther Freya Angelica; Wongsodiredjo, Jacklyn (UMSU, 2025)
Indonesia has just held elections for both the legislative and executive in 2024. In this year's elections, young voters from generation z dominated the number of voters. Therefore, many parties participating in the 2024 election are starting to pay attention to these young voters. Partai Keadilan Sejahtera (PKS) is one of the parties that has succeeded in gaining an increase in votes in the 2024 elections. This cannot be separated from their efforts to carry out digital PR for generation z. Therefore, this research aims to describe the digital PR strategy carried out by PKS in an effort to attract young voters. This research uses qualitative methods, case studies, with interviews and document studies as data collection methods. The results of this research show that there are four digital PR strategies used, namely Attracting Visitors through Search, Engagement Dialogue, Building Campaign Buzz, and Defensive/Crisis. This entire strategy is implemented in an integrated, sustainable manner so as to attract young voters.